Second harmonic generation in AB-type LaTiO3/SrTiO3 superlattices. (April 2021) - Zhao, Hui; An, Qichang; Ye, X.; Yu, B.H.; Zhang, Q.H.; Sun, F.; Zhang, Q.Y.; Yang, Fang; Guo, Jiandong; Zhao, Jimin
Abstract: We report the generation and control of second harmonic generation (SHG) from a series of LaTiO3 /SrTiO3 superlattices. We demonstrate that the nonlinear optical susceptibility χ (2) and the SHG pattern can be tuned by tailoring the number of superlattice interfaces. Significantly, unlike the conventional ABC-type nanostructures, our AB-type nanostructures can also produce SHG signals. The χ (2) value (24.3 pm/V) is even one to two orders of magnitude greater than the conventional ones. Hence, we demonstrate that SHG is a local microscopic process—it does not rely on macroscopic broken inversion symmetry. Moreover, we show that temperature dependence or structural phase transition can further enhance the SHG intensity. Our results introduce a scheme for SHG, extending the generation and control of SHG in nano-photonics to nearly all the accessible centrosymmetric materials. Graphical Abstract: ga1 Highlights: Overturn the previous belief that only non-centrosymmetric (such as the ABC-type) structures can generate SHG. Demonstrate that SHG is a purely microscopic local (down to atomic lattice distance) process. The χ (2) and SHG pattern can be tuned by tailoring the number of superlattice interfaces. Controlling temperature provides an additional degree of freedom for generating and controlling SHG.